The SGK1 inhibitor SI113 induces autophagy, apoptosis, and endoplasmic reticulum stress in endometrial cancer cells. Issue 12 (27th April 2017) - Conza, Domenico; Mirra, Paola; Calì, Gaetano; Tortora, Teresa; Insabato, Luigi; Fiory, Francesca; Schenone, Silvia; Amato, Rosario; Beguinot, Francesco; Perrotti, Nicola; Ulianich, Luca
Abstract : Endometrial cancer is often characterized by PI3K/AKT pathway deregulation. Recently it has been suggested that SGK1, a serine/threonine protein kinase that shares structural and functional similarities with the AKT family, might play a role in cancer, since its expression and/or activity has been found to be deregulated in different human tumors. However, the role of SGK1 in endometrial cancer has been poorly investigated. Here, we show that SGK1 expression is increased in tissue specimens from neoplastic endometrium. The SGK1 inhibitor SI113 induced a significant reduction of endometrial cancer cells viability, measured by the (3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide assay. This effect was associated to the increase of autophagy, as revealed by the increase of the markers LC3B‐II and beclin I, detected by both immunofluorescence and western blot analysis. SI113 treatment caused also apoptosis of endometrial cancer cells, evidenced by the cleavage of the apoptotic markers PARP and Caspase‐9. Intriguingly, these effects were associated to the induction of endoplasmic reticulum stress markers GRP78 and CHOP evaluated by both Real‐Time RT‐PCR and Western Blot analysis. Increased expression of SGK1 in endometrial cancer tissues suggest a role for SGK1 in this type of cancer, as reported for other malignancies. Moreover, the efficacy of SI113 in affecting endometrial cancer cells viability, possibly via endoplasmic reticulum stress activation, identifies SGK1 as an attractive molecular target for new tailored therapeutic intervention for the treatment of endometrial cancer. Abstract : SGK1 expression is increased in endometrial cancer SI113, an inhibitor of SGK1, induces endoplasmic reticulum stress, autophagy, and apoptosis in endometrial cancer cells.